Adipose-Derived Inflammatory and Coagulant Mediators in Patients With Sepsis. Issue 5 (May 2021) - Zwischenberger, Brittany A.; Balasuriya, Beverly K.; Harris, Dwight D.; Nataraj, Nisha; Owen, Allison M.; Bruno, Maria E. C.; Mukherjee, Sujata; Ortiz-Soriano, Victor; O'Connor, William; Ke, Chenlu; Stromberg, Arnold J.; Chang, Phillip K.; et al.
Abstract : ABSTRACT: Results from preclinical sepsis studies using rodents are often criticized as not being reproducible in humans. Using a murine model, we previously reported that visceral adipose tissues (VAT) are highly active during the acute inflammatory response, serving as a major source of inflammatory and coagulant mediators. The purpose of this study was to determine whether these findings are recapitulated in patients with sepsis and to evaluate their clinical significance. VAT and plasma were obtained from patients undergoing intra-abdominal operations with noninflammatory conditions (control), local inflammation, or sepsis. In mesenteric and epiploic VAT, gene expression of pro-inflammatory (TNFα, IL-6, IL-1α, IL-1β) and pro-coagulant (PAI-1, PAI-2, TSP-1, TF) mediators was increased in sepsis compared with control and local inflammation groups. In the omentum, increased expression was limited to IL-1β, PAI-1, and PAI-2, showing a depot-specific regulation. Histological analyses showed little correlation between cellular infiltration and gene expression, indicating a resident source of these mediators. Notably, a strong correlation between PAI-1 expression in VAT and circulating protein levels was observed, both being positively associated with markers of acute kidney injury (AKI). In another cohort of septic patients stratified by incidence of AKI, circulating PAI-1 levels were higher in those with versus without AKI, thus extending these findings beyond intra-abdominal cases. This study is the first to translate upregulation of VAT mediators in sepsis from mouse to human. Collectively, the data suggest that development of AKI in septic patients is associated with high plasma levels of PAI-1, likely derived from resident cells within VAT. Abstract : Supplemental Digital Content is available in the text